The Role Of Parents In Facilitating Children’s Learning In The Era Globalization Case Study Students Of SMP N 03 South Bengkulu - Joesa Yolandari; Zulyan; Anisia Nur Mitha Sari; Romadhona Kusuma Yudha; Rizki (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify the problems faced by low-income families in facilitating children's learning in the era of globalization, as well as to explain the efforts they can make to overcome their children's learning barriers. Using a qualitative approach. The findings of this study reveal that the problems faced by lower-middle-class families in facilitating children's learning in the era of globalization are; (1) Lack of funds to purchase learning equipment such as cellphones or laptops. (2) Limited time to accompany children in learning. (3) Lack of academic ability to teach children. (4) Facing mental stress due to job loss. Furthermore, efforts made by these families to overcome children's educational problems include; (1) Borrowing funds from cooperatives or relatives to obtain learning equipment. (2) Utilizing social assistance for low-income families and support for students such as KIP and KIS. This condition reflects that parents continue to try to provide children with learning tools and facilities in the era of globalization. This shows that low-income families struggle to ensure that their children continue to receive an education because with education they can improve the social status of their community for the better.